Pengaruh Konsentrasi Giberelin (GA3) terhadap Pertumbuhan Kailan (Brassica oleracea L. Var alboglabra) pada Berbagai Media Tanam dengan Hidroponik Wick System - Asih Maharani; Suwirmen Suwirmen; Zozy Aneloi Noli (Universitas Andalas, 2018)
Effect of giberelin (GA3) concentration on growth and yield of Chinese kale (Brassica oleracea L. Var alboglabra) in various medium using hydroponic wick system . This research conducted from April until July 2016 in Wire House and Plant Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Science, Andalas University. The purposes of this research were to obtain GA3 concentration and planting medium that accelerate growth and yield of Chinese kale and determine the interaction between GA3 and planting medium to the gowth and yield of Chinese kale planted using hydroponics wick system. This research used Completely Randomized Design (CRD) in factorial with three replications, as the first factor were concentration of GA3 (0 ppm, 20 ppm, 40 ppm and 60 ppm) and the second factor were medium (zeolite, sand, husk and sawdust). The best result in accelerated the growth of Chinese kale was the treatment at the concentration of 60 ppm GA3 and zeolite was suitable medium to Chinese kale growth. This research found the interaction between GA3 and medium on the length of the roots Chinese kale used hydroponic wick system.